Collimated Microbeam Reveals that the Proportion of Non-Damaged Cells in Irradiated Blastoderm Determines the Success of Development in Medaka (Oryzias latipes) Embryos - Takako Yasuda; Tomoo Funayama; Kento Nagata; Duolin Li; Takuya Endo; Qihui Jia; Michiyo Suzuki; Yuji Ishikawa; Hiroshi Mitani; Shoji Oda (Biology, 2020)
It has been widely accepted that prenatal exposure to ionizing radiation (IR) can affect embryonic and fetal development in mammals, depending on dose and gestational age of the exposure, however, the precise machinery underlying the IR-induced disturbance of embryonic development is still remained elusive. In this study, we examined the effects of gamma-ray irradiation on blastula embryos of medaka and found transient delay of brain development even when they hatched normally with low dose irradiation (2 and 5 Gy). In contrast, irradiation of higher dose of gamma-rays (10 Gy) killed the embryos with malformations before hatching. We then conducted targeted irradiation of blastoderm with a collimated carbon-ion microbeam. When a part (about 4, 10 and 25%) of blastoderm cells were injured by lethal dose (50 Gy) of carbon-ion microbeam irradiation, loss of about 10% or less of blastoderm cells induced only the transient delay of brain development and the embryos hatched normally, whereas embryos with about 25% of their blastoderm cells were irradiated stopped development at neurula stage and died. These findings strongly suggest that the developmental disturbance in the IR irradiated embryos is determined by the proportion of severely injured cells in the blastoderm.